Axial And Radial Loading Effects On Quasi-Static Crushing Of Glass/Epoxy Composite Tubes - Aziz Ameen, Haifaa (2003)
An experimental and finite element investigation of glass fiber/epoxy composite tubes were carried out under axial compressive and radial loading. A filament winding equipment has been used for the fabrication process of the specimens. These composite tubes were fabricated with 2,4,6 and 8 layers, keeping the fiber orientation angle of 90°, the tubes inner diameter is 50mm and the height is 100mm for all the specimens. Steel cones, of semi cone angle of 10, 20, 30 and 40 degrees were used to develop the axial and radial-loading cases. In addition, flat plate was used for pure axial crushing cases. The Volume fraction of glass fiber and matrix used was 70% and 30% respectively. The required properties for the composite used were obtained from a tensile test specimens and used for the theoretical part of this study to calculate the first crushing loads. The experimental tests for all the crushing tests of the composite tubes and the tensile specimens tests were performed at room temperature of 20° C .Three composite tubes were fabricated and tested for each number of layers and each loading case. Tests were carried out at a crushing speed of 2.5mm/min using a digital Instron testing machine of 250 kN capacity. The results obtained from this study include the experimental results of the load-displacement relations, the first crushing load, average crushing load, crushing load gradient and the energy absorption. On the other hand, only the buckling load has been obtained from the finite element part of this study.